The Common Good of Business: Addressing a Challenge Posed by «Caritas in Veritate» - Sison, Alejo G. (Journal of business ethics, 2011)
Caritas in Veritate (CV) poses a challenge to the business community when it asks for “a profoundly new way of understanding business enterprise” (CV 40). The paper proposes the concept of the “common good” as a starting point for the discussion and sketches a definition of the common good of business as the path toward an answer for this challenge. Building on the distinction between the material and the formal parts of the common good, the authors characterize profit as the material part of the common good of business and work as the formal part that expresses the essential significance of business.